On the action of cyclosporine A, rapamycin and tacrolimus on M. avium including subspecies paratuberculosis. - Robert J Greenstein; Liya Su; Ramon A Juste; Sheldon T Brown (PLoS ONE, 2008)
BACKGROUND: Mycobacterium avium subspecies paratuberculosis (MAP) may be zoonotic. Recently the "immuno-modulators" methotrexate, azathioprine and 6-MP and the "anti-inflammatory" 5-ASA have been shown to inhibit MAP growth in vitro. We concluded that their most plausible mechanism of action is as antiMAP antibiotics. The "immunosuppressants" Cyclosporine A, Rapamycin and Tacrolimus (FK 506) treat a variety of "autoimmune" and "inflammatory" diseases. Rapamycin and Tacrolimus are macrolides. We hypothesized that their mode of action may simply be to inhibit MAP growth. METHODOLOGY: The effect on radiometric MAP (14)CO(2) growth kinetics of Cyclosporine A, Rapamycin and Tacrolimus on MAP cultured from humans (Dominic & UCF 4) or ruminants (ATCC 19698 & 303) and M. avium subspecies avium (ATCC 25291 & 101) are presented as "percent decrease in cumulative GI" (%-DeltacGI.) PRINCIPAL FINDINGS: The positive control clofazimine has 99%-DeltacGI at 0.5 microg/ml (Dominic). Phthalimide, a negative control has no dose dependent inhibition on any strain. Against MAP there is dose dependent inhibition by the immunosuppressants. Cyclosporine has 97%-DeltacGI by 32 microg/ml (Dominic), Rapamycin has 74%-DeltacGI by 64 microg/ml (UCF 4) and Tacrolimus 43%-DeltacGI by 64 microg/ml (UCF 4) CONCLUSIONS: We show heretofore-undescribed inhibition of MAP growth in vitro by "immunosuppressants;" the cyclic undecapeptide Cyclosporine A, and the macrolides Rapamycin and Tacrolimus. These data are compatible with our thesis that, unknowingly, the medical profession has been treating MAP infections since 1942 when 5-ASA and subsequently azathioprine, 6-MP and methotrexate were introduced in the therapy of some "autoimmune" and "inflammatory" diseases.